2010
DOI: 10.1149/1.3484785
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical Study of Stainless Steel Corrosion in NaCl-KCl Melt

Abstract: High-temperature spectroelectrochemestry was applied to study corrosion of various types of stainless steel in molten salts. The electronic absorption spectra of products of anodic dissolution of stainless steel major components (iron, chromium, nickel, molybdenum, manganese, titanium) were measured in NaCl-KCl melt at 750 0 C. The effectiveness and limitations of applying spectroscopic method for studying alloys corrosion was demonstrated on example of anodic dissolution of AISI 316L, 316Ti and 321 austenitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Thus, as a result of formation of new excessive phases, the continuous γ-solid solution Ni-Cr-Mo is transformed into a three-phase system -grain of alloy | depleted in molybdenum zone | excessive phase. As the interaction process of multicomponent steels and alloys with molten chloride has an electrochemical nature (4,8,9), the depletion by the electropositive molybdenum zone will act as a anode of formed microgalvanic pairs in the obtained three-phase system during the contact with electrolyte. The most electronegative elements of anode zone formed galvanic element (such as chromium and manganese) will be etched from this region (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, as a result of formation of new excessive phases, the continuous γ-solid solution Ni-Cr-Mo is transformed into a three-phase system -grain of alloy | depleted in molybdenum zone | excessive phase. As the interaction process of multicomponent steels and alloys with molten chloride has an electrochemical nature (4,8,9), the depletion by the electropositive molybdenum zone will act as a anode of formed microgalvanic pairs in the obtained three-phase system during the contact with electrolyte. The most electronegative elements of anode zone formed galvanic element (such as chromium and manganese) will be etched from this region (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The described influence is caused by unavoidable high temperature exposure in contact with molten salts for a prolonged period of time. Previously our group showed that the main reason of intergranular corrosion in molten chlorides is the sensitization effect resulting in formation of excessive carbide phases at the grain boundaries (9). The formation of heterophase structure leads to appearance of microgalvanic pairs and acceleration of corrosion processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining spectroscopy with electrochemistry in spectroelectrochemistry is particularly valuable for the interrogation and control of conditions present in the salt. Spectroelectrochemistry has been used in molten salt systems for both its ability to determine speciation and for controlling the oxidation states of specific species within these systems (Nagai et al, 2005;Polovov et al, 2007;Volkovich et al, 2007;Polovov et al, 2008;Abramov et al, 2010;Nagai et al, 2011;Park et al, 2011;Nagai et al, 2013;Schroll et al, 2016). Corrosion products such as Cr, Fe, Ni, Mo, Ti, and Mn have been studied using spectroelectrochemical methods (Volkovich et al, 2007;Abramov et al, 2010).…”
Section: Online Monitoring Of Systems That Contribute To Off-gas Loadingmentioning
confidence: 99%
“…The absence of titanium in the surface layer can be explained by the formation of inclusions of titanium carbide and carbonitride in the bulk of steel. It was shown that such compounds do not dissolve in contact with the electrolyte but can transfer to the melt as solid particles in a result of spalling (21). The determined kinetic dependencies of sample weight change and corrosion rate for 08Kh17T in molten NaCl-KCl-VCl 2 salt at 750 0 C are presented in Figures 2 and 3, respectively.…”
Section: Corrosion Of Ferritic Steel 08kh17 In Nacl-kcl-vcl 2 Meltsmentioning
confidence: 99%